Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
(-2,3)
Step-by-step explanation:
In order to solve the system using substitution, one of the variables must be defined so we can substitute it into the other equation.
We can easily define x in the second first by adding 2y from both sides
x - 2y = - 8
* add 2y to both sides *
x = 2y - 8
Now that we have defined x in the first equation we can plug in the defined value of x into the second equation
6x + 7y = 9
substitute 2y - 8 for x
6 (2y - 8) + 7y = 9
distribute 6 to -2y and -8
6 * 2y = 12y
6 * -8 = -48
12y - 48 + 7y = 9
combine like terms ( 12y + 7y = 19y )
19y - 48 = 9
add 48 to both sides
19y = 57
divide both sides by 19
19y/19 = y and 57/19 = 3
we're left with y = 3
Now that we have found the value of one of the variables we can plug it in to one of the equations ( note that plugging the value of y and solving for x in either equation will lead us to the same answer ) and solve for the other variable (x)
x - 2y = -8
y = 3
x - 2(3) = -8
multiply -2 and 3
x - 6 = -8
add 6 to both sides
x = -2
so x = -2 and y= 3
Therefore the solution to the system of equations is (-2,3)
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.